Crosstalk between exosomes and tumor-associated macrophages in hepatocellular carcinoma: implication for cancer progression and therapy - Xu, Ying; Xu, Linyue; Chen, Qiuyan; Zou, Can; Huang, Ju; Zhang, Limei (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC), the most prevalent type of primary liver cancer, represents a significant cause of cancer-related mortality. While our understanding of its pathogenesis is comparatively comprehensive, the influence of the tumor microenvironment (TME) on its progression warrants additional investigation. Tumor-associated macrophages (TAMs) have significant impacts on cancer cell proliferation, migration, invasion, and immune response, facilitating a complex interaction within the TME. Exosomes, which measure between 30 and 150 nanometers in size, are categorized into small extracellular vesicles, secreted by a wide range of eukaryotic cells. They can transfer biological molecules including proteins, non-coding RNAs, and lipids, which mediates the intercellular communication within the TME. Emerging evidence has revealed that exosomes regulate macrophage polarization, thus impacting cancer progression and immune responses within the TME of HCC. Moreover, TAM-derived exosomes also play crucial roles in malignant transformation, which hold immense potential for cancer therapy. In this review, we elaborate on the crosstalk between exosomes and TAMs within TME during HCC development. Moreover, we delve into the feasible treatment approaches for exosomes in cancer therapy and emphasize the limitations and challenges for the translation of exosomes derived from TAMs into clinical courses for cancer therapy, which may provide new perspectives on further ameliorations of therapeutic regimes based on exosomes to advance their clinical applications.